G340(P) The use of simulation to support out of programme paediatric trainees. (24th May 2017) - Thompson, L; Kirk, N; McCay, N
Abstract : Background: Many Paediatric trainees in Northern Ireland (NI) take time out of programme (OOP), most commonly maternity leave. Trainees can feel anxious, de-skilled and under-confident on returning to work. 1, 2 However there is little evidence describing these difficulties and limited targeted support available for OOP trainees. We aimed to identify the needs and concerns of OOP paediatric trainees, and subsequently develop a course to provide education and support to these trainees. Method: We developed an online questionnaire for all paediatric trainees in NI who had spent time OOP, to identify any issues the trainees had experienced. We combined this with our own experience and a review of courses in other deaneries, to develop a pilot 'Return to Acute Paediatrics' course. This course was held on a half day in July 2015, and all OOP trainees were invited to attend. The programme included short lectures on 'hot topics in paediatrics' and neonatal/paediatric simulation including acute clinical scenarios and resuscitation using the simulation suite facilities. The effectiveness of our programme was assessed using pre- and post-course questionnaires. Results: 7 eligible trainees attended, and all were OOP due to maternity leave. All trainees rated the course as 'excellent', with 100% recording improved confidence in managing acute scenarios following the course. The main feedback request was for more neonatal and paediatric simulation, and so the course has been extended to a full day to provide more simulation opportunities. Conclusion: Returning to clinical practice following time OOP can be difficult and there was previously no targeted educational support available for OOP paediatric trainees in NI. We have demonstrated that our pilot 'Return to Paediatrics' course has resulted in improved confidence in managing acute paediatric scenarios. This course is now held twice a year through the deanery, using simulation to facilitate a less daunting return to acute Paediatrics. References: Brightwell A, Minson S, Ward A, Fertleman C. Returning to clinical training after maternity leave. BMJ Careers. 2013; 09.10 Available from: http://careers.bmj.com/careers/advice/Returning_to_clinical_training_after_maternity_leave Academy of Royal Colleges. Returning to clinical practice background document. Academy of Royal Colleges, April 2012 Available from: http://www.aomrc.org.uk/publications/reports-a-guidance